TWO NEW SUBSPECIES OF TROPAEOLUM (TROPAEOLACEAE) FROM THE IV REGION (COQUIMBO), CHILE - Watson, John M.; Flores, Ana R. (Gayana Botánica, 2000)
Two new subspecies of Tropaeolum hookerianum Barn. are described. Apart from T. hookerianum subsp. austropurpureum presented here, only one other Andean-Pacific temperate Tropaeolum, T. azureum Bert. ex Colla, has blue to purple flowers. The second taxon, T. hookerianum subsp. pilosum, is distinguished by pilose pedicels, a feature unique among Andean-Pacific temperate species. Both novelties are Chilean endemics restricted to the IV Region (Coquimbo), as also is the nominate subspecies. All three are allopatric, and considered together extend the species' range to the north, to the south and to the east. Their characters and interrelationships pose implications for Tropaeolum evolution which are likely to be of interest to exponents of phylogenetics (cladistics), phenetics (taxometrics) and other disciplines. Descriptions and a key are provided, and aspects of morphology, ecology and distribution discussed.